Blackhorse riders eaudiobook A desperate last stand, an extraordinary rescue mission, and the vietnam battle america forgot. - Keith, Philip (Tantor Media, 2012)
Deep in the jungles of Vietnam, Alpha Troop, 1st Squadron, 11th Armored Cavalry, the famed Blackhorse Regiment, was a specialized cavalry outfit equipped with tanks and armored assault vehicles. On the morning of March 26, 1970, they began hearing radio calls from an infantry unit four kilometers away that had stumbled into a hidden North Vietnamese Army stronghold. Outnumbered at least six to one, the ninety-man American company was quickly surrounded, pinned down, and fighting for its existence. Helicopters could not penetrate the dense jungle, and artillery and air support could not be targeted effectively. The company was fated to be worn down and eventually all killed or captured. Overhearing the calls for help on his radio, Captain John Poindexter, Alpha Troop's twenty-five-year-old commander, realized that his outfit was the only hope for the trapped company. It just might be possible that they could "bust" enough jungle by nightfall to reach them. Not making the attempt was deemed unacceptable, so he ordered his men to "saddle up." With the courage and determination that makes legends out of ordinary men, they effected a daring rescue and fought a pitched battle—at considerable cost. Many brave deeds were done that day and Captain Poindexter tried to make sure his men were recognized for their actions. Thirty years later Poindexter was made aware that his award recommendations and even the records of the battle had somehow gone missing. Thus began the second phase of this remarkable story: a "battle" to ensure that his brave men's accomplishments would never be forgotten again. The full circle was completed when President Obama stepped to the podium on October 20, 2009, to award the Alpha Troop with the Presidential Unit Citation: the highest combat award that can be given to a military unit.